Leguminous Lectins as Tools for Studying the Role of Sugar Residues in Leukocyte Recruitment - N. M. N. Alencar; E. H. Teixeira; A. M. S. Assreuy; B. S. Cavada; C. A. Flores; R. A. Ribeiro (Mediators of Inflammation)
The natural physiological ligands for selectins are oligosaccharides found in glycoprotein or glycolipid molecules in cell membranes. In order to study the role of sugar residues in the in vivo lectin anti-inflammatory effect, we tested three leguminous lectins with different carbohydrate binding affinities in the peritonitis and paw oedema models induced by carrageenin in rats. L. sericeus lectin was more anti-inflammatory than D. virgata lectin, the effects being reversed by their specific binding sugars (N-acetylglucosamine and α-methylmannoside, respectively). However, V. macrocarpa, a galactose-specific lectin, was not anti-inflammatory. The proposed anti-inflammatory activity of lectins could be due to a blockage of neutrophil-selectin carbohydrate ligands. Thus, according to the present data, we suggest an important role for N-acetylglucosamine residue as the major ligand for selectins on rat neutrophil membranes.